The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.4049/jimmunol.1401986
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbated Experimental Colitis in TNFAIP8-Deficient Mice

Abstract: The TNF-α-induced protein 8 (TNFAIP8 or TIPE) is a risk factor for cancer and bacterial infection, and its expression is upregulated in a number of human cancers. However, its physiological and pathological functions are unclear. We describe here the generation of TIPE-deficient mice and their increased sensitivity to colonic inflammation. TIPE-deficient mice were generated by germ line gene targeting and were born without noticeable developmental abnormalities. Their major organs including lymphoid organs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…3). This is consistent with our previous report that C57BL/6 mice deficient in either TIPE2 or TNFAIP8 alone do not have significant changes in their total lymphocyte numbers in lymphoid organs under the steady state (before 10 weeks of age) 24,27 . These results indicate that, under steady state, directed migration is critical for T cell deployment to lymphoid organs, and that random migration (which can be significantly enhanced by chemokines) also plays an important role in leukocyte deployment to lymphoid organs.…”
Section: Tnfaip8 Is a Carrier Protein Of Phosphoinositide Second Messsupporting
confidence: 93%
“…3). This is consistent with our previous report that C57BL/6 mice deficient in either TIPE2 or TNFAIP8 alone do not have significant changes in their total lymphocyte numbers in lymphoid organs under the steady state (before 10 weeks of age) 24,27 . These results indicate that, under steady state, directed migration is critical for T cell deployment to lymphoid organs, and that random migration (which can be significantly enhanced by chemokines) also plays an important role in leukocyte deployment to lymphoid organs.…”
Section: Tnfaip8 Is a Carrier Protein Of Phosphoinositide Second Messsupporting
confidence: 93%
“…37 Knocking out the TNFAIP8 gene also exacerbated disease in a dextran sodium sulfate (DSS) model of murine colitis, and the data suggested that this effect was due to decreased epithelial cell survival in the face of the chemical insult. 38 Knocking down TNFAIP8 also excacerbates oxidative stress-mediated autophagic cell death in a manner involving decreased mTOR activation. 39 In contrast to the aforementioned studies, the downregulation of TNFAIP8 has also been shown to prevent glucocorticoid-mediated apoptosis in thymocytes.…”
Section: Introductionmentioning
confidence: 99%
“…The DAI for each animal was recorded once after every 5-day DSS administration period for the first two DSS cycles, and then every day starting after the third DSS cycle. Scores were determined based on body weight loss, stool consistency, and rectal bleeding as described previously (Sun et al, 2015). Body weight loss was scored as follows: score 0, no body weight loss; score 1, body weight loss within 1%−5%; score 2, body weight loss within 5%−10%; score 3, body weight loss within 10%−20%; score 4, greater than 20% body weight loss.…”
Section: Star ★ Methodsmentioning
confidence: 99%